2021
DOI: 10.1590/1678-5150-pvb-6773
|View full text |Cite
|
Sign up to set email alerts
|

Differentials in the epidemiological profile of canine visceral leishmaniasis in the semi-arid region of Paraíba, Brazil

Abstract: The objective of this study was to estimate the prevalence of canine visceral leishmaniasis (CVL) and to identify the differences in associated factors to its occurrence in urban area and countrysides in the municipality of Santa Luzia located in the semi-arid region of Paraíba. In the years 2015 and 2016, 779 blood samples from dogs were collected. The prevalence was determined by three serological techniques, ELISA-S7® Kit, DPP® Rapid Test and EIE-LVC® Kit, considering positive the samples that reacted in at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“… 14 In order to understand the epidemiology of canine leishmaniasis, many studies were dedicated to serological investigation, where they found the presence of Leishmania antibodies in the analyzed samples. 15 21 Other studies showed the participation of dogs in the process of urbanization 22 , 23 and resurgence of leishmaniasis, 22 as well as suggesting that the disease is expanding in urban areas, with an exponential increase of positivity within dogs. 24 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 14 In order to understand the epidemiology of canine leishmaniasis, many studies were dedicated to serological investigation, where they found the presence of Leishmania antibodies in the analyzed samples. 15 21 Other studies showed the participation of dogs in the process of urbanization 22 , 23 and resurgence of leishmaniasis, 22 as well as suggesting that the disease is expanding in urban areas, with an exponential increase of positivity within dogs. 24 …”
Section: Resultsmentioning
confidence: 99%
“…14 In order to understand the epidemiology of canine leishmaniasis, many studies were dedicated to serological investigation, where they found the presence of Leishmania antibodies in the analyzed samples. [15][16][17][18][19][20][21] Other studies showed the participation of dogs in the process of urbanization 22,23 and resurgence of leishmaniasis, 22 as well as suggesting that the disease is expanding in urban areas, with an exponential increase of positivity within dogs. 24 In addition, according to López et al 25 besides the characteristics and behaviors of dogs, their relationship with environmental conditions and disorderly occupations are relevant to the high prevalence of leishmaniasis.…”
Section: Resultsmentioning
confidence: 99%